Subcutaneous immunoglobulin preserves muscle strength in chronic inflammatory demyelinating polyneuropathy. (7th July 2014) - Markvardsen, L. H.; Harbo, T.; Sindrup, S. H.; Christiansen, I.; Andersen, H.; Jakobsen, J.; The Danish CIDP and MMN Study Group
<x xml:space="preserve">Abstract</x> Background and purpose Subcutaneous immunoglobulin (SCIG) is superior to placebo treatment for maintenance of muscle strength during 12 weeks in patients with chronic inflammatory demyelinating polyneuropathy (CIDP). The present study evaluated whether SCIG preserves muscle strength for 1 year in an open‐label follow‐up study. Methods Seventeen responders to intravenous immunoglobulin (IVIG) who had participated in the previous study of SCIG versus placebo in CIDP were included. After one IVIG infusion 2 weeks prior to baseline, all continued on SCIG treatment at weekly equal dosage and were evaluated after 3, 6 and 12 months. Primary end‐points were changes in muscle strength evaluated by isokinetic dynamometry in four affected muscle groups and a composite score of muscle performance and function tests, including Medical Research Council (MRC) score, grip strength, 40‐m walking test (40‐MWT) and nine‐hole peg test (9‐HPT). Secondary end‐points were changes of each of the listed parameters at each time point as well as an overall disability sum score (ODSS). Results The dose of SCIG was significantly unaltered during the follow‐up period. Overall the isokinetic dynamometry value increased by 7.2% (P = 0.033) and after 3, 6 and 12 months by 5.7%, 8.2% and 6.8% (ns). The overall composite score at all time intervals and for each interval remained unchanged. Amongst the secondary parameters the MRC score increased significantly by 1.7% (P = 0.007), whereas grip strength, 40‐MWT, 9‐HPT and ODSS remained unchanged. Conclusion SCIG preserves muscle strength and functional ability in patients with CIDP who previously responded to IVIG. SCIG should be considered as an alternative in long‐term treatment of CIDP patients.